Dynamic range expansion leads to establishment of a new, genetically distinct wolf population in Central Europe - Szewczyk, Maciej; Nowak, Sabina; Niedźwiecka, Natalia; Hulva, Pavel; Špinkytė-Bačkaitienė, Renata; Demjanovičová, Klára; Bolfíková, Barbora Černá; Antal, Vladimír; Fenchuk, Viktar; Figura, Michał; Tomczak, Patrycja; Stachyra, Przemysław; et al. (Scientific reports, 2019)
Local extinction and recolonization events can shape genetic structure of subdivided animal populations. The gray wolf (Canis lupus) was extirpated from most of Europe, but recently recolonized big part of its historical range. An exceptionally dynamic expansion of wolf population is observed in the western part of the Great European Plain. Nonetheless, genetic consequences of this process have not yet been fully understood. We aimed to assess genetic diversity of this recently established wolf population in Western Poland (WPL), determine its origin and provide novel data regarding the population genetic structure of the grey wolf in Central Europe. We utilized both spatially explicit and non-explicit Bayesian clustering approaches, as well as a model-independent, multivariate method DAPC, to infer genetic structure in large dataset (881 identified individuals) of wolf microsatellite genotypes. To put the patterns observed in studied population into a broader biogeographic context we also analyzed a mtDNA control region fragment widely used in previous studies. In comparison to a source population, we found slightly reduced allelic richness and heterozygosity in the newly recolonized areas west of the Vistula river. We discovered relatively strong west-east structuring in lowland wolves, probably reflecting founder-flush and allele surfing during range expansion, resulting in clear distinction of WPL, eastern lowland and Carpathian genetic groups. Interestingly, wolves from recently recolonized mountainous areas (Sudetes Mts, SW Poland) clustered together with lowland, but not Carpathian wolf populations. We also identified an area in Central Poland that seems to be a melting pot of western, lowland eastern and Carpathian wolves. We conclude that the process of dynamic recolonization of Central European lowlands lead to the formation of a new, genetically distinct wolf population. Together with the settlement and establishment of packs in mountains by lowland wolves and vice versa, it suggests that demographic dynamics and possibly anthropogenic barriers rather than ecological factors (e.g. natal habitat-biased dispersal patterns) shape the current wolf genetic structure in Central Europe.
Keywords: Wolves; zeměpis; haplotypy; populační genetika; mitochondriální DNA; migrace zvířat; Ecosystem; vlci; Genetics, Population; Geography; Microsatellite Repeats; DNA, Mitochondrial; Haplotypes; Cluster Analysis; zvířata; Europe; genetická variace; Genetic Variation; Animal Migration; shluková analýza; Bayesova věta; mikrosatelitní repetice; Animals; Bayes Theorem; Evropa; ekosystém